2015
DOI: 10.1016/j.worlddev.2014.07.008
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Empowerment in a Capability-Based Poverty Approach: Evidence from The Gambia

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 30 publications
(40 reference statements)
1
34
0
2
Order By: Relevance
“…A large body of literature shows how access to and control over productive resources are positive contributors to women's empowerment (FAO 2011;Kabeer 1999;Trommlerová et al 2015). The World Bank (2009) found that the lower productivity of fields owned by women and girls relates to their limited access to productive resources (especially land), technologies and information.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
See 1 more Smart Citation
“…A large body of literature shows how access to and control over productive resources are positive contributors to women's empowerment (FAO 2011;Kabeer 1999;Trommlerová et al 2015). The World Bank (2009) found that the lower productivity of fields owned by women and girls relates to their limited access to productive resources (especially land), technologies and information.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
“…Access to and control of livestock has contributed to women's empowerment, especially in livestock-dependent communities like those involved in the MoreMilkiT project (Flintan 2008;Trommlerová et al 2015). In her study across Indonesia, Bolivia, Peru and Kenya, Valdivia (2001), shows that women's control over livestock, livestock products and the productive resources needed to raise livestock, increases women's bargaining power, access to animal source foods that they use mostly to benefit their children and ultimately their empowerment.…”
Section: Dimensions Of Empowerment In the Welimentioning
confidence: 99%
“…Despite extensive debate and reconceptualisation of the 'empowerment' concept in international development over the last 40 years, no single, clear definition has emerged (Trommlerová, Klasen, & Lessmann, 2015). One approach follows the suggestion by Ibrahim and Alkire (Ibrahim & Alkire, 2007) to view empowerment as an expansion of 'agency freedom', or just 'agency', an construct integral to the Capability Approach founded by Amartya Sen (1985).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A lot of previous research on women's empowerment has mainly focused on the determinants of women's empowerment indicators which mainly include household decision-making and self-esteem (El-Halawany, 2009;Ghuman et al, 2004;Kishor 2000, Kishor andSubaiya, 2008;Mahmud and Tasmeen, 2014;Mahmud et al, 2012;Malhotra and Mather, 1997;Sado et al, 2014;Trommlerova et al, 2015). Measuring a dynamic process like women's empowerment necessitates indicators that measure the end result, that is, indicators that measure evidence of empowerment and indicators that measure various sources of empowerment as well as indicators for measuring the setting of empowerment (Kishor, 2000).…”
Section: Some Major Theories On Women's Empowermentmentioning
confidence: 99%